Birefringent lateral Goos-Hänchen effect through chiral medium. (31st July 2020) - Khan, Sajid; Muhammad, Saleh; Bacha, Bakht Amin; Wahid, Umer
Abstract: Birefringence of lateral Goos-Hänchen (GH) shift in reflection and transmission beams are investigated through four level chiral atomic medium. Significant positive and negative shifts in reflection and transmission birefringence beams are reported under the strength of driving fields. At resonance point, positive birefringent shifts of 2.8 λ and 2 λ are noted in reflection beams. The birefringence lateral GH-shift in transmission beams show contrast behaviors of −2 λ and −2.8 λ at resonance point. A 30% fractional change in birefringent reflection and transmission beams with GH-shift are investigated. These results will play a vital role in the modification of optical heterodyne sensors technology, cloaking devices, image coding, integrated optical technologies and telecom industry.